Temperature‐Regulated Turnover of Chromophoric Dissolved Organic Matter in Global Dark Marginal Basins. Issue 19 (28th September 2021) - Wang, Chao; Guo, Weidong; Li, Yan; Dahlgren, Randy A.; Guo, Xianghui; Qu, Liyin; Zhuang, Wei
Abstract: Oceanic absorption of heat generated by greenhouse gas emissions has resulted in warming of the dark ocean (>200 m) that contains a large refractory DOM (RDOM) pool. However, changes in microbially mediated production and degradation dynamics for RDOM components in response to warming of dark marginal basins remain unclear. Herein, we integrated data from the dark South China, Mediterranean and Japan Seas (temperature range: 0.09–15.1°C) to demonstrate that in situ production efficiency of two ubiquitous humic‐like fluorophores increased at higher dark ocean temperature, whereas chromophores at a wavelength of 325 nm ( a CDOM (325)) changed from production to degradation at higher temperature. Increased oxygen consumption and a reduction of labile substrates in future warmer dark ocean environments may initiate the final degradation of some semi‐refractory components, thereby increasing the recalcitrance of RDOM, but decreasing the DOM inventory in dark basins and creating a positive feedback to rising atmospheric CO2 . Plain Language Summary: Marine refractory dissolved organic matter (RDOM) in the dark ocean is primarily formed during heterotrophic degradation of labile organic matter, which has a pronounced sensitivity to temperature variation. Since the 1960s, the global dark ocean has exhibited an accelerated warming with a discernable temperature increase. Thus, determining the importance of temperature on microbial regulation of the oceanic RDOM pool is of great significance. This study utilized the ocean interior of the marginal South China, Mediterranean and Japan Seas as natural basin‐scale enclosed incubators along with optical DOM characterization methods to reveal a production‐degradation reaction series for RDOM components. A decrease in the DOM inventory by enhanced microbial mineralization (producing CO2 ) in a warmer dark ocean may create a positive feedback in response to global climate change. Key Points: Faster turnover for optical components of dissolved organic matter (DOM) was observed in dark marginal basins than in the open ocean In situ production efficiency of two ubiquitous humic‐like fluorophores increased at higher dark ocean temperatures An increase of DOM recalcitrance and decrease of the bulk dissolved organic carbon pool may occur due to a future warming of dark basins